Legal Vacuum in Indigenous Peoples' Legal Representation Regarding Communal Land Rights - Devin Jinoto (JUSTISI, 2026)
The aim of this study is to critically examine the normative vacuum regarding the civil representation of indigenous peoples in Indonesia, with a particular focus on disputes over communal land rights The method used is a normative legal approach by examining legislative instruments, jurisprudence, and analysis of selected cases, which aims to reveal systemic weaknesses in the legal recognition of indigenous peoples' representatives in the national legal structure. The novelty lies in its direct involvement in unresolved issues regarding the legitimacy of indigenous community representation in formal judicial and administrative processes, a dimension that has often been overlooked in previous legal studies. The results of the study propose a reform agenda that includes formal legal recognition of customary leadership structures, the establishment of regulatory norms based on the principle of Free, Prior, and Informed Consent (FPIC), and the adjustment of civil law principles to better reflect the customary-based collective governance systems that exist within indigenous communities and Informed Consent/FPIC), and the adjustment of civil law principles to better reflect the collective customary-based governance system that prevails within indigenous communities. The conclusion of the research is that in order to respond to these challenges, this paper proposes a reform agenda that includes formal legal recognition of traditional leadership structures, the establishment of regulatory norms based on the principles of Free, Prior, Prior, and Informed Consent (FPIC) principles, and the adjustment of civil law principles to better reflect the collective and customary governance systems common among indigenous communities.